Against Ordentlikheid: Disobedient Femininities in Selected Embroideries by Hannalie Taute. Issue 1 (2nd January 2020) - Sonnekus, Theo
ABSTRACT: This article explores the art practice of Hannalie Taute vis-à-vis the discourses of ordentlikheid (respectability) and the volksmoeder (mother of the nation). I begin by offering theoretical frameworks for these discursive structures, as well as a selective historical trajectory of their development, with major emphasis on Afrikaner femininity and Afrikaner women's domestic labour. Through a reading of selected embroidered works by Taute, I speculate on the degree to which the artist revisits and subverts particular narratives of Afrikaner ethnic identity and "women's work" to imagine new modes of feminine expression that challenge the rigid conventions of ordentlikheid and the volksmoeder . My analysis of Taute's embroidery is informed by the concept of radical decadence, which provides a theoretical paradigm for making sense of the strategic use of excess, pleasure, and the taboo in the practices of contemporary women artists working with craft materials. The works were thus selected for their materiality and thematics, which I argue appropriate archaic signifiers of Afrikaner femininity to produce irreverent counter-narratives that resist the policing of female sexuality and other forms of patriarchal subjugation.